Rapid suppression of HBV replication before related liver transplantation in a patient with HDV superinfection. Clinical case report - U. R. Salimov; P. Balachandran; D. B. Tulyaganov; M. R. Ruzibakieva; F. A. Khadjibaev; K. E. Anvarov (Вестник трансплантологии и искусственных органов, 2024)
Chronic hepatitis B virus (HBV) infection is one of the main problems of modern transplantology and transplant hepatology, often leading to potentially fatal complications. The only definitive treatment for HBV-related cirrhosis is liver transplantation. However, recurrence of HBV after transplantation may jeopardize both recipient and graft survival. Therefore, all HBsAg-positive recipients should receive prophylactic therapy with nucleos(t)ide analogues with or without hepatitis B immune globulin (HBIG), regardless of the hepatitis B e-antigen (HBeAg) status and HBV DNA level before transplantation. However, HBIG therapy has a number of disadvantages, and nucleos(t) ide analogues do not inhibit replication of super and co-infection. In addition, there is no unified understanding of the time limits for achieving a virologic response. In our clinical case, we report a rapid suppression (5 days) of high HBV (560,000 copies/mL) viral load in a patient suffering from HBV- and HDV-related cirrhosis, who was operated on with positive HBeAg at the time of transplantation. In our study, the use of standard therapy tenofovir disoproxil fumarate reduced the HBV viral load titer to undetectable values. In turn, given the positiveHBeAg at the time of transplantation, HBV infection recurred in the early post-transplant period, which was eliminated without the use of HBIG therapy. The use of tenofovir disoproxil fumarate makes it possible to plan transplantation for patients with positive replication and high viral load, avoiding the use of HBIG, against the background of limited liver transplant wait time.